Edaravone attenuates neuronal apoptosis in hypoxic-ischemic brain damage rat model via suppression of TRAIL signaling pathway. (June 2018) - Li, Chunyi; Mo, Zhihuai; Lei, Junjie; Li, Huiqing; Fu, Ruying; Huang, Yanxia; Luo, Shijian; Zhang, Lei
Abstract: Background and objectives: Edaravone is a new type of oxygen free radical scavenger and able to attenuate various brain damage including hypoxic-ischemic brain damage (HIBD). This study was aimed at investigating the neuroprotective mechanism of edaravone in rat hypoxic-ischemic brain damage model and its correlation with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) signaling pathway. Materials and methods: 75 seven-day-old Sprague-Dawley neonatal rats were equally divided into three groups: sham-operated group (sham), HIBD group and HIBD rats injected with edaravone (HIBD + EDA) group. Neurological severity and space cognitive ability of rats in each group were evaluated using Longa neurological severity score and Morris water maze testing. TUNEL assay and flow cytometry were used to determine brain cell apoptosis. Western blot was used to estimate the expression level of death receptor-5 (DR5), Fas-associated protein with death domain (FADD), caspase 8, B-cell lymphoma-2 (Bcl-2) and Bcl-2 associated X protein (Bax). In addition, immunofluorescence was performed to detect caspase 3. Results: Edaravone reduced neurofunctional damage caused by HIBD and improved the cognitive capability of rats. The above experiment results suggested that edaravone could down-regulate the expression of active caspase 3 protein, thereby relieving neuronal apoptosis. Conclusion: Taken together, edaravone could attenuate neuronal apoptosis in rat hypoxic-ischemic brain damage model via suppression of TRAIL signaling pathway, which also suggested that edaravone might be an effective therapeutic strategy for HIBD clinical treatment.